Comparative analysis of disseminated and structurally controlled gold deposits of the Juruena Mineral Province integrating geological and geophysical data - Coura Filho, Luiz Eduardo Faria (2024)
The Juruena Mineral Province (PMJ), located in the southern part of the Amazonian Craton, consists of sequences of Paleoproterozoic magmatic arcs. In this region, primary occurrences of Au ±Cu ±metals occur in various styles, including disseminated and vein-hosted types. This study compares disseminated and structurally controlled deposits within the PMJ, exemplified by the Luizão and Aguinaldo deposits, respectively. This work aimed to discern the main gamma-ray spectrometry and magnetic characteristics of these deposits for future exploratory work. To achieve this goal, open gamma-ray spectrometry and magnetic field data from the Brazilian Geological Service (SGB-CPRM) were used. Both deposits exhibit strong magnetic signals, located on the periphery of magnetic anomalies. The regional distribution of lineaments and apparent deformation of the sources of the magnetic contrasts collectively reveal at least two distinct stages of deformation. The first phase consists of a Riedel-type shear system (N30E, N80E, and N70W), characterized by simple shear with a notable compressive component. The second phase is associated with the reactivation of shear zones from phase 1, also under simple shear conditions, but with a normal component. The Luizão deposit is situated at the boundary between two distinct gamma-spectrometric units, corresponding to the North and South Facies of the Novo Mundo Granite. In the South Facies, high K counts and anomalies in F parameter suggest the extension of potassium alteration at the surface. The Luizão region exhibits low magnetic interconnectivity of the lineaments associated with the first deformational phase. The main lineament in the region (N70W), characterized as P shear, and the magnetic anomaly are located at the lithological contact. The last phase of deformation at Luizão is characterized by shallow lineaments oriented N30E. In the Aguinaldo region, there is high interconnectivity of lineaments such as the x and y joints, which control the location of the associated magnetic anomaly. The deposit is situated on a regional lineament characterized as R\', and a series of shallow lineaments oriented N30E, N80E, and N70W cut through the deposit. Near Aguinaldo, the high F parameter points to a possible hydrothermal contribution. Our work provides contrasting key factors in different mineralization styles, contributing with tools for future exploration.